ANALISIS PERHITUNGAN DAN PELAPORAN PAJAK PENGHASILAN PASAL 21 PADA PT. GATRA KALTIM JAYA KOTA BALIKPAPAN - Dewanata, Pandu; Tinangon, Jantje J.; Wokas, Heince R. N. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2013)
Company as a tax cutter has a very big role for the government. Currently there's a few companies that implement the tax deductions are not consistent with applicable regulations. This is caused by the company which considers the tax as a cost that the company will minimize the costs to optimize their profit. It is necessary good cooperation between the government and the company for the sake of continuity of the tax deduction . PT. GATRA KALTIM JAYA engaged in General trading in Balikpapan City has provided the highest satisfaction to the customers by providing the best quality products and innovative services on time. In this satisfying PT. GATRA KALTIM JAYA need qualified employees in order to achieve company goals. Therefore as an appreciation for services provided by its employees, the company gave contra such as wages and salaries also benefits as well as some additional bonuses. So, PT. GATRA KALTIM JAYA is obliged to withhold income tax  of salary employees' salary Article 21. The analytical method used in this research is descriptive research. The results are PT. News in Brief KALTIM JAYA Balikpapan in doing calculations, deductions and tax reporting of Income Tax  Article 21 of  the employee already complianced with the provisions of Law Taxation. No. 36 of 2008.